Radical vs conservative treatment of intraosseous ameloblastoma: Systematic review and meta‐analysis. (1st January 2019) - Hendra, Faqi Nurdiansyah; Natsir Kalla, Diandra Sabrina; Van Cann, Ellen M.; de Vet, Henrica C. W.; Helder, Marco N.; Forouzanfar, Tymour
Abstract: Objectives: The aim of the present study was to assess the outcomes of radical and conservative treatment approaches of solid/multicystic and unicystic ameloblastoma in terms of recurrence rates. Material and methods: A systematic review and meta‐analysis was conducted based on the PRISMA statement. Search was performed using PubMed, Embase, SCOPUS, and Web of Science for articles published from January 1969 until March 2018. Quality assessment of the selected articles was conducted using the Quality Appraisal of Case Series Studies Checklist. The meta‐analysis was performed using the MedCalc program. Results: The search strategy yielded 6, 984 articles; 20 studies met the eligibility criteria and were included in the meta‐analysis. The pooled recurrence rate of solid/multicystic ameloblastomas following radical treatment was 8%, while conservative treatment caused recurrences in 41%. For unicystic ameloblastomas, these values were 3% and 21%, respectively. The risk of recurrences in both types of ameloblastomas following radical treatment was lower than following conservative treatment. Conclusions: The present study showed statistically significant differences in recurrence favoring radical treatment for both unicystic and solid/multicystic ameloblastoma. The solid/multicystic type showed more recurrences than the unicystic type. Unfortunately, since only retrospective studies were available, the evidence is less strong as wished for.